Stress and marital satisfaction of married Middle Eastern students in Malaysia - Vaez, Elham; Juhari, Rumaya (SAGE Journals, 2017)
This study examined the relationship between stress and marital satisfaction from the perspective of the vulnerability–stress–adaptation model. We hypothesised that some stress factors were associated with lower marital satisfaction. Making use of the structure equation modeling, the results of data analysis on 462 Middle Eastern students in Malaysia, supported the hypotheses of our study and showed that a higher level of stress is strongly related to a negative marital satisfaction. Moreover, the results indicated that marital stress is the strongest stressors that negatively affect the marital satisfaction of the respondents. This research provides a general view of stressors that have an impact on the marital satisfaction of married Middle East students who live as sojourners in Malaysia.